The sovereignty paradox: Brexit's territorial consequences for Gibraltar, Scotland and Nothern Ireland - Jaume Castan Pinos; Jeremy Sacramento (Danish Institute for International Studies (DIIS), 2020)
The United Kingdom formally left the European Union on 31 January 2020, following the Brexit referendum of June 2016. One of the central arguments used by "leave" supporters in the run up to the referendum concerned UK sovereignty in the sense of "taking back control" and restoring decision-making powers over the country's affairs. The UK's departure from the bloc, however, has revealed a striking paradox in that it appears to compromise the most fundamental aspect of sovereignty: territorial integrity. This DIIS Working Paper argues that Brexit has revived territorial debates in the British peripheries that had arguably been settled prior to the referendum. In order to illustrate this argument, the paper draws on three cases and their respective territorial challenges: secession in Scotland, Spanish annexation of Gibraltar, the reunification of Ireland. The paper daringly claims that Brexit has created the essential conditions for these territorial transformations to materialise.
Keywords: 330; Foreign policy; EU External Relations; Europe & North America; United Kingdom